Study of the Influence of Morphology and Strength of Interphase Boundaries on the Integral Mechanical Properties of NiCr-TiC Composite; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Eremina G. M. Galina; Smolin A. Yu. Alexey; Shilko E. V. Evgeny Viktorovich; Psakhie S. G. Sergey Grigorievich (2016, 2016)
Title screen